Harmonisasi Agama dan Budaya dalam Pendidikan Islam Multikultural : Harmonizing Religion and Culture in Multicultural Islamic Education - Jajat Darojat; Novianti, Cucum (CV Kalimasada Group, 2025)
This paper discusses the issue of cultural and religious diversity in Indonesia and the urgency of multicultural Islamic education as a solution to social conflicts with SARA backgrounds. Issues such as radicalism, group fanaticism, and intergroup violence show a weak understanding of the plurality of Indonesian society. Historically, religious and ethnic conflicts have left a dark record, showing the importance of an inclusive and tolerant perspective in social life. Education has a strategic role not only to educate, but also to shape cultured and noble human beings. This paper uses a social phenomenology approach and literature study and ethnography methods to explore how the transformation of religious values can be done through culture. The author emphasizes the importance of multicultural education in Islamic education as a medium to shape students' inclusive attitudes. Acculturation between culture and religion is seen as a form of dialectic between divine revelation and the social reality of society. Islam, as a universal religion, is not present in an empty cultural space, but rather dialogues and transforms with local culture. In this context, education becomes a strategic space to reconstruct a harmonious understanding of religion and culture, in order to create a peaceful, tolerant and civilized society. This study is presented as a reflection on social anxiety and the challenges of education in responding to the complexity of life in a multicultural society in Indonesia.